Socio-Economic Relations and Patriarchal Culture with the Incident of Unmet Need - Nursafira Fitriyan; Hasrida Hasrida (GLOBAL HEALTH SCIENCE GROUP, 2025)
Unmet need is a condition when women of childbearing age have a need to use contraception but it is not met. This condition can occur in women who do not want to have any more children or want to space out pregnancies, but do not use contraception. This study aims to analyze the relationship between socio-economic and patriarchal culture and the incidence of unmet need for family planning. Method: Uses a cross-sectional design with quantitative methods. The population consists of fertile couples (PUS) at the Siti Khadijah Clinic, with a sample of 60 respondents taken using a purposive sampling technique. Data were collected using a Standard questionnaire and analyzed using the chi-square test. Results: The analysis shows that Respondents with a low economic level are more vulnerable to experiencing unmet need, as shown by the significant value between socioeconomic (p=0.001) and patriarchal culture (p=0.000) with the incidence of unmet need. Conclusions: Socio-economic and patriarchal culture play a significant role in the incidence of unmet need for family planning. Cultural-based interventions and economic empowerment programs are needed to increase access and participation of fertile couples in family planning service programs as well as assistance and guidance to prospective family planning participants.